1992
DOI: 10.1111/j.1600-0528.1992.tb01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the likelihood of successful decisions to treat dentin caries from bitewing radiographs

Abstract: The purpose of this study was to describe the role played by the ability to estimate caries depth in successfully deciding to treat dentin caries when making use of bitewing radiographs as a diagnostic test. A 10% random sample (n = 444) of Dutch dental practitioners was sent a two-wave questionnaire concerning radiographic caries diagnosis and restorative treatment decision making. The second wave consisted of simulated bitewing radiographs of 105 tooth surfaces with and without dentin caries according to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 26 publications
1
22
1
1
Order By: Relevance
“…43, 44 Dawson et al 45 hypothesized that diagnosis of periapical lesion is not influenced by diagnostic confidence; dentists who feel confident about diagnosing pathology from radiographs are not necessarily able to correctly diagnose the lesion. 46 This was proven in a study by Stheeman et al 47 where a dentist's ability to diagnose a radio-opaque lesion was independent of their diagnostic confidence and their diagnostic ability increased when they were more confident regarding the lesion when confronted with a radiograph. In agreement with these studies, our results show that there was significant variation in what the practitioner said they will be detecting from the radiograph and what they were able to detect from the radiographs provided.…”
Section: Discussionmentioning
confidence: 87%
“…43, 44 Dawson et al 45 hypothesized that diagnosis of periapical lesion is not influenced by diagnostic confidence; dentists who feel confident about diagnosing pathology from radiographs are not necessarily able to correctly diagnose the lesion. 46 This was proven in a study by Stheeman et al 47 where a dentist's ability to diagnose a radio-opaque lesion was independent of their diagnostic confidence and their diagnostic ability increased when they were more confident regarding the lesion when confronted with a radiograph. In agreement with these studies, our results show that there was significant variation in what the practitioner said they will be detecting from the radiograph and what they were able to detect from the radiographs provided.…”
Section: Discussionmentioning
confidence: 87%
“…[15][16][17][18] Attempts have been made to maintain inter-examiner and intra-examiner consistency by means of intensive training. [19][20][21] Previous studies have concluded that it is possible to train dentists in order to achieve high levels of inter-examiner consistency and to maintain these levels after 12 months, although the results are somewhat inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is not surprising that investigators report substantial disagreement among dentists who have examined the same radiographs, about which teeth require approximal restorations [Bader and Shugars, 1992;Elderton and Nuttall, 1983;Kay et al, 1992;Mileman et al, 1992]. This divergence in treatment planning is not the result of different philosophies of restorative intervention, but primarily of different abilities to perceive the presence and extent of radiographic caries in an objective, consistent manner [Kay et al, 1992;Mileman et al, 1992].…”
mentioning
confidence: 99%
“…This divergence in treatment planning is not the result of different philosophies of restorative intervention, but primarily of different abilities to perceive the presence and extent of radiographic caries in an objective, consistent manner [Kay et al, 1992;Mileman et al, 1992]. Further, it is evident that these differences in diagnostic ability and the resulting therapy inevitably result in some incorrect and inappropriate treatment [Rytömaa et al, 1979].…”
mentioning
confidence: 99%
See 1 more Smart Citation